From Customer Intimacy to Digital Customer Intimacy - Qianhua Liu; Ka-Ching Chan; Ranga Chimhundu (Journal of Theoretical and Applied Electronic Commerce Research)
Customer intimacy plays a crucial role in shaping customer relationships and guiding organizational strategies. As the digital business environment has grown, the concept of customer intimacy has evolved, leading to significant changes in its dimensions and implications. This systematic literature review and synthesis comprehensively analyzes the current research on customer intimacy, reexamines it within the context of e-commerce and digital marketing, and introduces the concept of “Digital Customer Intimacy”. The paper explores the unique characteristics of digital customer intimacy, how it differs from traditional customer intimacy, and identifies areas for future research. By synthesizing insights from various studies, this review deepens our understanding of customer intimacy in both traditional and digital contexts, offering practical insights for modern marketing and laying the groundwork for future research.